2017
DOI: 10.1080/10942912.2017.1326055
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation and discrimination of flavouring process of garlic-flavoured vegetable oils

Abstract: In this study, the effects of two garlic-flavouring processes on quality parameters and the organosulphur compound profile were investigated. The results showed that the addition of fresh garlic increased acidity and peroxide values in all flavoured vegetable oils. Mono-, di-, and trisulphides were mainly present in aromatised oils, while allicin, ajoene, and vinyldithiins were found in macerated oils. Analyses of the principal components demonstrate that flavoured oils could be discriminated according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Among them, GSP5 has the highest level of volatiles (37.944 μg/g), which is about 5 times higher than GSP1 (7.692 μg/g). This result was similar to Gonzalez (2017), who showed that different processing conditions significantly affected the flavor quality of garlic‐flavored products 23 . Among the quantified volatiles present in GSPs, sulfur‐containing compounds were the largest groups; detailed information on the major families of volatiles in the five GSPs is described as follows.…”
Section: Resultssupporting
confidence: 88%
“…Among them, GSP5 has the highest level of volatiles (37.944 μg/g), which is about 5 times higher than GSP1 (7.692 μg/g). This result was similar to Gonzalez (2017), who showed that different processing conditions significantly affected the flavor quality of garlic‐flavored products 23 . Among the quantified volatiles present in GSPs, sulfur‐containing compounds were the largest groups; detailed information on the major families of volatiles in the five GSPs is described as follows.…”
Section: Resultssupporting
confidence: 88%
“…A number of previous investigations describe the aromatization of olive oils with different sources of natural bioactive ingredients such as olive leaves, olive pomace, herbs and spices (red pepper, lavender, laurel, chili, garlic, rosemary, basil, thyme, mint, oregano, etc) fruits (lemon, orange, etc), truffles, licopen, seaweed, walnuts, fish oil, etc (Damechki et al, 2001;Bendini et al, 2002;Ayadi et al, 2009;Sousa et al, 2015;Baiano et al, 2016;González et al, 2017;Campo et al, 2018;Kasimoglu et al, 2018). Aromatization methods include traditional maceration, maceration with the application of ultrasound (Assami et al, 2016) or microwaves (Benmousa et al, 2016), extraction of different compounds (by solid-liquid extraction, liquid-liquid extraction, or supercritic extraction) from the material and incorporation of the extract into the oil, and, finally, co-processing during milling or malaxation (Clodoveo et al, 2016;Yilmazer et al, 2016;Sacchi et al, 2017;Sena-Moreno et al, 2018;Issaoui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting maceration with additional treatments allows you to significantly shorten the maceration time from several weeks to several or several minutes [ 6 , 10 ]. The maceration process can be supported by mixing [ 11 ], homogenization [ 5 , 12 ] and the use of ultrasound [ 6 , 10 , 13 ], or microwave heating [ 14 ]. Various herbs and spices (fresh and dried) are most often used to flavor edible oils [ 7 , 8 , 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various herbs and spices (fresh and dried) are most often used to flavor edible oils [ 7 , 8 , 9 , 11 ]. So far, the studies have produced and tested macerates with rosemary, sage, summer savory, laurel, oregano, garlic, basil, thyme, lavender, menthe, chill pepper [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Among the plants used for maceration and aromatization of oils, rosemary has proven to be one of the most suitable herbs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation